Regional protection of human rights - Shelton, Dinah (Oxford University Press, 2013)
The international protection of human rights is generally recognized as a fundamental aim of modern international law. Even a cursory review of legal systems for the protection of human rights demonstrates the rapid expansion of this field since the end of World War II. During this period, nearly all global and regional organizations have adopted human rights standards and addressed human rights violations by member states. As a consequence, no state today can claim that its treatment of those within its jurisdiction is a matter solely of domestic concern. In Regional Protection of Human Right.